2022
DOI: 10.26434/chemrxiv-2022-7f7x2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of 1-benzhydryl piperazine-based HDAC inhibitors with anticancer and antimetastatic properties against human breast cancer: synthesis, molecular modeling, in vitro and in vivo biological evaluation

Abstract: Selective histone deacetylase 6 (HDAC6) inhibition is promoted as a rational strategy to develop safer anticancer drugs compared to nonselective HDAC inhibitors. Nevertheless, considerably more nonselective HDAC inhibitors have been undergoing clinical trials. Initially, we focused on synthesizing a selective HDAC6 inhibitor, with 1-benzhydryl piperazine as surface recognition CAP group, and its nonselective analogues with small structural perturbations in the hydrocarbon linker. Surprisingly, the in vitro HDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have shown that HDAC6 might be of dual function in the regulation of both AD and cancer. Ruzic et al 's (2022) study discovered two HDAC6 inhibitors with anti-breast cancer activity. As for AD, HDAC6, has shown elevated levels in AD with direct interaction with the tau protein (Qureshi and Chinnathambi, 2022) while Sreenivasmurthy et al 's (2022) study shows that inhibiting HDAC6 leads to activation of chaperone-mediated autophagy and alleviation of tau pathology in AD models.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that HDAC6 might be of dual function in the regulation of both AD and cancer. Ruzic et al 's (2022) study discovered two HDAC6 inhibitors with anti-breast cancer activity. As for AD, HDAC6, has shown elevated levels in AD with direct interaction with the tau protein (Qureshi and Chinnathambi, 2022) while Sreenivasmurthy et al 's (2022) study shows that inhibiting HDAC6 leads to activation of chaperone-mediated autophagy and alleviation of tau pathology in AD models.…”
Section: Discussionmentioning
confidence: 99%